A Case Report on Eosinophilic Hepatitis with Hypereosinophilic Syndrome (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Eosinophilic hepatitis could be labelled as one of the rarest cause of acute hepatitis. It is itself a part of another rare disorder called hypereosinophilic syndrome (HES), which constitute a hetergenous group of disorders, defined as persistent and marked blood eosinophilia (>1.5x109/L) associated with proof of eosinophil mediated end organ damage and exclusion of other cause of eosinophilia. Although the condition itself is rare but it is not rare to have hepatic involvement in HES as it can happen upto one-third of patients with HES. Excessive aggregation of eosinophils in the liver leading to inflammation and damage is regarded as eosinophilic hepatitis. Here we present a case of HES with eosinophilic hepatitis in a patient, who presented with pyrexia of unknown origin and abdominal pain. J Bangladesh Coll Phys Surg 2025; 43: 243-249